PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS PENGUNJUNG DI DAYA TARIK WISATA TAMAN BUAH MEKARSARI BOGOR - Nova Eviana; Lenny Yusrini (Eduturisma, 2016)
The purpose of this study is to determine the effect of product quality and service quality on satisfaction and loyalty of visitors in Mekarsari tourist attractions Bogor. The study is a survey using a questionnaire developed by the underlying theories of quality product, quality service, customer satisfaction and customer loyalty. In the early stages, theoretical validation is conducted toward 30 respondents. Validity and reliability test results show there are 6 items declared invalid and should be eliminated. Data is collected using simple random sampling technique involving 175 respondents by theory of Slovin based on the reasonable population of 300 people. Testing is done using path analysis with the assistance of SPSS ver. 20. The results show that both variables of product quality and service quality influence simultaneously and contribute 43.4% toward visitors’ satisfaction. The contribution of exogenous variables, namely product quality, service quality and visitors’ satisfaction toward of visitors’ loyalty as endogenous variable is 46.6%. Partially only variables of quality products and quality services significantly affect the visitors’ loyalty.